(untitled) (LEARNing Landscapes, 2016)
This paper explores how students in a Quebec university encounter world humanitarian crises within the context of a refugee camp in Jordan, explored from the perspective of co-creation within a design class workshop.1 Students2 create solutions together in groups, using a project-based approach that incorporates collaborative learning and integrate aesthetic thinking with ethical and sustainable proposals that consider humanity within camps. They develop potentially usable solutions that are then presented to experts in the humanitarian community. The workshop goals, learning activities, and results are presented with three examples of student projects. In this type of learning environment, project-based approaches frame co-creation and collaborative learning.